2016
DOI: 10.1038/srep26747
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal APCs of the endogenous nanomineral pathway fail to express PD-L1 in Crohn’s disease

Abstract: Crohn’s disease is a chronic inflammatory condition most commonly affecting the ileum and colon. The aetiology of Crohn’s disease is complex and may include defects in peptidoglycan recognition, and/or failures in the establishment of intestinal tolerance. We have recently described a novel constitutive endogenous delivery system for the translocation of nanomineral-antigen-peptidoglycan (NAP) conjugates to antigen presenting cells (APCs) in intestinal lymphoid patches. In mice NAP conjugate delivery to APCs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…This may underlie the PD‐L1 overexpression in these diseases, as we observed. Indeed, PD‐L1 epithelial expression has been described in a small number of IBD, 20 UC 21 and CD cases 22 . Additionally, and in line with our findings, increased PD‐L1 epithelial expression has also been described in pancreatic ductal cells of patients with type 2 autoimmune pancreatitis, a condition that is often associated with UC, and thus probably pathogenetically related 23…”
Section: Discussionsupporting
confidence: 89%
“…This may underlie the PD‐L1 overexpression in these diseases, as we observed. Indeed, PD‐L1 epithelial expression has been described in a small number of IBD, 20 UC 21 and CD cases 22 . Additionally, and in line with our findings, increased PD‐L1 epithelial expression has also been described in pancreatic ductal cells of patients with type 2 autoimmune pancreatitis, a condition that is often associated with UC, and thus probably pathogenetically related 23…”
Section: Discussionsupporting
confidence: 89%
“…However, those studies where performed mostly by flow cytometry, where selective enrichment and gating of the professional immune cells did not include CMF analysis. Furthermore, a deficiency in professional antigen-presenting cells PD-L1 induction was reported in small intestinal lymphoid patches in CD ( 25 , 26 ). We confirmed that PD-L1 was moderately increased in the UC and CD epithelial cells as has been previously seen by Nakazawa et al ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intricate role of PD-L1 and PD-L2 in the dysregulation of Th cell responses in human IBD remains unclear and the sparse reports are contradictory. PD-L1 is upregulated in the intestinal epithelium, macrophages, and B cells in both forms of IBD ( 21 , 24 ), yet expression of inducible PD-L1 appears to be impaired in CD-derived monocytes and ileal APCs ( 25 , 26 ). Finally, recent reports indicate that while mAbs against PD-1 and anti-PD-L1 are currently successfully used in clinics for treatment of several solid tumors, one of the main immune-related adverse effect (irAE) of the immune checkpoint blockade therapy is development of chronic diarrhea and enterocolitis ( 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the AMCP is inert, its cargo (notably peptidoglycan) appears to actively promote tolerance in the normal gut by up-regulating the co-regulatory molecule, PD-L1, on APCs that are recipients of endogenous cargo-bearing AMCP 17, 33. However, this is not the case in Crohn's disease 41 . We have recently shown that APCs of the AMCP pathway display a selective failure in expression of PD-L1 in this disorder 41 and hence hypothesized that this may lead to a loss of tolerance towards luminal contents—a hallmark of the disease 42 .…”
Section: Discussionmentioning
confidence: 99%